Study of the laser marking process of cold sprayed titanium coatings on aluminium substrates. (September 2016) - Astarita, A.; Genna, S.; Leone, C.; Memola Capece Minutolo, F.; Squillace, A.; Velotti, C.
Abstract: This paper deals with the study of the laser marking process of titanium cold sprayed coatings on aluminium substrates. Despite several studies regarding the laser marking process are available in literature very few attention have been paid to the marking of cold sprayed coatings and there are no previous papers in literature. Also the phenomena occurring during the marking of a porous coating are to date not fully understood and will be discussed in this paper. The experimental campaign was also repeated on grade 2 titanium rolled sheets with a thickness of 2 mm. The marking tests were carried out under different experimental conditions varying the main process parameters (i.e. laser pulse power and laser scan speed), after that the mark sections were observed by optical microscope and SEM. Both the maximum penetration depth and width of the marks were acquired and also internal damages induced by the process were studied. A correlation between the process parameters and the mark's geometry was found. The results show the effectiveness of the laser process to produce high quality marks on both the titanium layer and the titanium sheet. Moreover, a higher mark penetration on Ti coating was observed compared to the Ti sheet. However, the results show also the possibility to introduce severe and hidden damages in both materials if the process parameters are not properly set. Highlights: The laser marking process of a cold sprayed titanium coating was studied. Different processing conditions were found. The microstructure and the hidden damages induced by the marking process were studied. Optimal processing conditions were found.